Ibn Khaldun on discipline - ABDULLAH M. ALWAGDAN (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This paper looks at Ibn Khaldun’s main works to see what he says about discipline. It argues that it is the central idea behind his studies of cultural, economic, and social phenomena. This demonstrates, more narrowly, that discipline is major to his widely acclaimed analysis of asabiyyah.Method: What follows is a survey of a selection of these studies, illustrating how they incorporate discipline into their analyses and interpretations of asabiyyah.Findings: Subordination of self-interest to group interest, obedience to social orders, self-denial, and self-] restraint are all themes that emerge from his substantive writings as central aspects of the discipline. The texts also demonstrate how unquestioned an assumption Ibn Khaldun makes about the incompatibility of discipline and luxury.Implications/Novel Contribution: One of the most important areas of study to which Abdurrahman Ibn Khaldun (1332-1406) devoted his time and energy was asabiyyah (social solidarity). This study expands our understanding of Ibn Khaldun’s writings significantly.